Major Limb Amputations: A Tertiary Hospital Experience In Northwestern Cameroon - Johnson Alegbeleye, Bamidele (HEALTH SCIENCES AND DISEASE, 2020)
Objectives. The study aimed to describe the current pattern and outcome of care at a tertiary hospital in Shisong-Cameroon and to compare our experience with that of other published data. Methods. This observational prospective hospital-based study was conducted over the two years of 2018 to 2019. The parameters reviewed include sociodemographic data like the age and sex of the patients, then the indications for the major limb amputation, and the complications. Results. The study was carried out on 172 files of patients aged 1year to 84years with a mean age of 32± 10.28 years. There were 124 (72.4%) patients of the male, and 48 (21.6%) patients were of the female gender. One hundred seventy-two amputations were realized with Lower limb amputations were 99 (57.7%) in the lower extremity, and 73 (42.3%) in the upper extremity. There were 16 patients (9.30%) with complications, including surgical site infection of the stump wound closely trailed by hematoma. The most significant risk factor for amputation was diabetes (38 patients, 22.09%) followed by ulcer (2 patients, 1.16%), and vascular disease (6 patients, 3.49%). Traumatic gangrene was the most frequently encountered indication for amputation n = 104 (60.47%), followed by diabetic gangrene n = (38 patients, 22.09%). Conclusion. Traumatic gangrene and other trauma-related limb conditions are the leading indications for amputation in this study. Trauma is mostly preventable, and so there is a need for continued intensification of the public campaign on-road use as a means of preventing severe limb injuries and thus reducing the consequent need for amputations.